Conservação de tijolo cerâmico em alvenarias históricas : subsídios para restauração do sítio histórico de Santa Leopoldina-ES - Florenzano, Luciana da Silva (2016)
Primitive Middle East farming communities introduce the use of clay to enable shelter, building their cities initially with raw clay bricks dried in the sun and then burning them in kilns, turning raw clay into ceramic material. Therefore, the ceramic bri